2017
DOI: 10.21767/2471-9854.100032
|View full text |Cite
|
Sign up to set email alerts
|

War Trauma, Anxiety, and Resilience among University Students in the Gaza Strip

Abstract: The aims of this study were to identify the types of the traumatic experiences, to find the type of resilience factors, anxiety trait and state occurrence, and to determine the relationship between exposure to the traumatic experiences, resilience and trait and state among university students. It is a descriptive analytical study; the sample consisted of randomly selected 399 university students enrolled in the main four universities in Gaza Strip (Al-Aqsa, Al-Azhar, Al-Quds Open and Islamic University) at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
1
0
1
Order By: Relevance
“…Studies conducted in this context indicate the prevalence of psychological disorders such as anxiety among females more than males due to living in an environment of war and conflict ( Murthy & Lakshminarayana, 2006 ). These results are consistent with the results of Thabet and Sultan (2016) study conducted on a sample of university youth victims of war and conflict, which indicates that there is a relationship between anxiety and sex of war-affected young and that exposure to previous traumatic events due to armed conflict has long-term negative effects on university students that differ according to their gender this may increase their mental health problems. Also this result is consistent with a study conducted on the relationship between COVID-19 and future anxiety.…”
Section: Discussionsupporting
confidence: 90%
“…Studies conducted in this context indicate the prevalence of psychological disorders such as anxiety among females more than males due to living in an environment of war and conflict ( Murthy & Lakshminarayana, 2006 ). These results are consistent with the results of Thabet and Sultan (2016) study conducted on a sample of university youth victims of war and conflict, which indicates that there is a relationship between anxiety and sex of war-affected young and that exposure to previous traumatic events due to armed conflict has long-term negative effects on university students that differ according to their gender this may increase their mental health problems. Also this result is consistent with a study conducted on the relationship between COVID-19 and future anxiety.…”
Section: Discussionsupporting
confidence: 90%
“…The results indicated that both men (40%) and women (40%) had high scores of PCL (a score more than 48) which was higher than PTSD symptoms rates among potentially traumatic events exposed undergraduate students in other studies (Anders et al 2012;Frazier et al 2009;Watson and Haynes 2007). In addition, when compared to the similar studies conducted on individuals and students who live in or near conflict zones (Fontana et al 1992;Khan et al 2016;Marthoenis et al 2018;Şar 2017;Thabet and Abu Sultan 2016;Yasan et al 2008), the symptomology rates were higher in the current study. There are some possible reasons of the high rate of prevalence.…”
Section: Discussioncontrasting
confidence: 71%